Mini Review: The Potential of Piperine in Black Pepper in Improving Brain Work - Dandy Dewanto P; Putri Kinanthi; Naila Sistharani; Nurul Aqidatul; Dewi Yuniasih (Universitas Ahmad Dahlan, 2021)
This study aims to determine the effect of piperine as an antidepressant and the potential to improve brain cognitive function. Researchers conducted a literature review related to piperine's potential for brain work using databases such as PubMed, Google Scholar, Cochrane Library. Search the relevant research literature using the keywords